I’m not sure which you mean so I’m going to do both of them.
13) -(3x-7)-5x
First you’d distribute the -1 to (3x-7).
-1•3x= -3x
-1•-7= 7
Now it is -3x+7-5x
You’d add the like terms, which in this case, would be the x.
-3x-5x= -8x
Therefore the final, simplified answer would be -8x+7
15) -10(8-2k)+2k
You’d distribute the -10 to (8-2k) which ends up becoming -80+20k
-10•8= -80
-10•-2k= 20k
Now it becomes -80+20k+2k
Add the like terms and the simplified answer would be -80+22k
I hope this helped! :)